Universal Metrics to Characterize the Performance of Imaging 3-D Measurement Systems With a Focus on Static Indoor Scenes - Bastian Stahl; Alexandra Mielke; Robert Lange (IEEE Open Journal of Instrumentation and Measurement)
Imaging 3-D measurement systems differ not only in design, power consumption, and resolution but, most notably, in their measurement performance, which is rarely documented in a reproducible or comparable manner. In this work, we introduce a simple, universal methodology for quantitatively characterizing indirect time-of-flight cameras, focusing on point cloud data acquired under reproducible conditions. Our metrics build upon the ISO 5725-1 standard and related research to enable standardized comparisons across different systems, independent of their measurement principles. Beyond trueness, accuracy, and precision, we propose additional metrics to evaluate surface texture quality, addressing visually disruptive systematic measurement errors. We condense these measurements into 14 key metrics for a straightforward camera comparison. In addition, we introduce the energy-density-weighted depth precision index (EPI) as a metric to relate an active measurement system’s performance to the emitted optical power. Finally, we demonstrate the applicability of our methodology by evaluating seven state-of-the-art 3-D systems.